Responses to Hospital Restrictions on Family Visits during the COVID-19 Epidemic in Mali and France - Abdourahmane Coulibaly; Fanny Chabrol; Laurence Touré; Renyou Hou; Boubacar Sidiki Ibrahim Dramé; Kate Zinszer; Valéry Ridde (Taylor & Francis Group, 2023)
ABSTRACTFew studies have focused on the presence of families in the hospital in the context of an epidemic. The present study aims to contribute to filling this gap by answering the following question: How did professionals, patients and their families cope with more or less drastic restrictions to family visits and presence during the COVID-19 pandemic in a French and a Malian hospital during the COVID-19 pandemic? Data were collected during the first two waves of the pandemic through 111 semi-structured interviews (France = 55, Mali = 56). Most of the interviews were conducted with staff (n = 103), but also with families in the case of Mali (n = 8). The investigators also conducted 150 days of field observations, 44 in France and 106 in Mali. Thematic analysis was applied using an inductive approach. Interviews were content analyzed to identify passages in the interviews that were relevant to these different themes. The study highlighted the difficulty for the medical-clinical system to provide appropriate responses to the many emotional needs of patients in a pandemic context. Families in France benefited from a support service to reduce stress, while in Mali, no initiative was taken in this sense. In both countries, families often used the telephone as an alternative means of communicating with relatives. The results showed that in the two contexts, the presence and involvement of the families contributed to a better response to the patients' psycho-affective demands and thus promoted resilience in this field.